Predictive Factors of Potential Malignant Transformation in Recurrent Calcifying Cystic Odontogenic Tumor: Review of the Literature - Sepideh Mokhtari; Zhaleh Mohsenifar; Maedeh Ghorbanpour (Case Reports in Pathology)
Calcifying cystic odontogenic tumor (CCOT) demonstrates considerable diversity in histopathology and clinical behavior. Ghost cell odontogenic carcinoma (GCOC) is the rare malignant counterpart of CCOT and it frequently arises from malignant transformation of a recurrent CCOT. In this paper, we present a case of CCOT and discuss its distinct histopathologic features in recurrence. Then, we will have a review on clinical, histopathological, and immunohistochemical aspects of GCOC in the literature. Predictive factors of malignant transformation in a benign CCOT will also be discussed.